Bulletin 87 Houses For Mining Towns - Joseph H. White (The National Institute for Occupational Safety and Health (NIOSH), 1914)
In its investigations looking to the improvement of health condi- tions and the increase of efficiency in the mining industry, the Bureau of Mines, in cooperation with the Bureau of Public Health, is studying sanitary conditions in and about mines with the intent of pointing out how those conditions that are a menace to the health of the miner may be most efficiently removed or remedied. An out- line of sanitary betterment work at mining villages in the Birming- ham district of Alabama has already been published by the bureau," and in this bulletin are presented suggestions on the planning of mining towns and the construction of miners' houses. The bulletin does not pretend to be a treatise on the so-called "housing problem," and mentions sociologic issues only incidentally. It is assumed that the influence of proper shelter on health is understood and that not a lack of appreciation so much as a lack of knowledge of the best remedies is responsible for many of the undesirable conditions that exist at mining towns. The purpose of this bulletin is to supply facts on the building of well-lighted, well- ventilated, warm, attractive, and economical houses for miners, these houses being assumed to be units of an industrial village or town the building and management of which are under the control of a corporation, so that special conditions hold which do not apply to houses built and owned by individual miners. From this it is not to be inferred that the company-controlled town is the best system or the only one in vogue. The discussion of this side of the subject in all its phases is too involved to be included in this paper. One element in favor of the company-controlled town is its possible immediate responsiveness. Hence this assumption. Also the assumption is made that a-new isolated town is being built, and hence the selection of the site, the arrangement of the streets, and the situation of the houses are discussed before the house itself is treated, for one of the most important factors in obtaining an economical sanitary house is a well-selected town site. Many of the suggestions, however, may be applied in improving conditions in existing towns, in building new houses in old towns, or in repairing old houses. Emphasis must be laid on the fact that as a rule a mining village has a shorter life than a manufacturing town. Economy is emphasized frequently because the discussion is predi- cated upon the assumption that the miner himself is to pay for all that he gets. House rent will doubtless be expected to bring in a reasonable return on all money invested in streets, sidewalks, water supply, sewer system, and houses; in other words, the town is to be run on a business and not on a paternal or charitable basis. "Fair and reasonable" precludes, of course, the idea of excessive returns. Some companies do not consider it good policy to realize as high a rate of interest as an independent realty company would be war- ranted in realizing. Under some circumstances part of the town improvements might be charged as "expense of the industry," that is, to the consumer. The isolation of a mining town introduces a unique responsibility. As the miners are practically obliged to rent the company houses, the officials of the company ought to scrutinize all expenditures in- volved so that house rent may be reduced to a minimum. In a way the town builders are placed in the position of trustees. They deter- mine, within certain limits, what proportion of a man's wages shall be spent on house rent. This consideration should restrain fanciful and unnecessarily expensive building; the other extreme should like- wise be avoided. True economy should be distinguished from cheap- ness. Ugly, insanitary, uncomfortable shacks should not be built even if, because of their cheapness, there is a demand for them from tenants. The obligation of the industry to society as a whole as well us to the tenant ought to forbid this. A cheerful, strong, healthy, virile race will not rise out of the filth and squalor of cheap hovels. An insanitary environment often does its damage slowly and silently; vitiated air does not, like mine gas, announce its deadly work by an explosion. As Talbot⚫ says: Health depends in part on freedom from infection. The probability of obtain- ing that freedom will be greatly increased by maintaining the body at a high state of vigor, or "vitality," as it is popularly called. This implies the promo- tion of all agencies which have to do with the physical well-being as well as with the control of sources of infection. Many men realize that in building houses for their workmen they are invested with a peculiar responsibility that must be wielded wisely, and in large developments they call into consultation the land- scape architect, the sanitary engineer, and the building architect, as well as the mining engineer.